Pomacentrus bangladeshius, a new species of damselfish (Perciformes, Pomacentridae) from Saint Martin’s Island, Bangladesh - Habib, Kazi Ahsan; Islam, Md Jayedul; Nahar, Najmun; Neogi, Amit Kumer (Zootaxa, 2020)
A new species of damselfish, Pomacentrus bangladeshius, is described from 3 specimens, 67–77 mm standard length (SL), collected from Saint Martin’s Island, Bangladesh. The new species is distinguished from congeners in having the following combination of characters: XIV, 13 dorsal-fin elements; II, 14 anal-fin elements; 19 pectoral-fin rays; 18–19 lateral-line scales; 17–19 gill rakers on first arch; body depth 1.68–1.88 (1.88) in SL; snout 4.17–4.60 (4.17) in head length; head 2.91–3.09 (3.08) in SL; a prominent notch present between preorbital and suborbital; olive to dark brown body color, dark brown premaxilla, and yellow iris with a narrow bronze eye ring. The new species inhabits shallow reef flats around rock and coral outcrops. Phylogenetic analysis also shows the clear divergence of P. bangladeshius from other genetically closely related congeneric species retrieved from GenBank and that it represents a separate lineage.